USO DA ESPECTROSCOPIA FOTOACÚSTICA NO INFRAVERMELHO MÉDIO EM ESCAMAS DA ESPÉCIE ASTYANAX FASCIATUS. - De Lima, Vitor; Ávila, Cristiane; Marcio, Sandro; Andrade, Luis Humberto; Rondon, Yzel (ANAIS DO ENIC, 2018)
-